Menuju Green Society dengan Pemberdayaan Masyarakat di Desa Tlogohaji - Ardana Putri Farahdiansari (LPMP Imperium, 2023)
Community service through Kuliah Kerja Nyata (KKN) is a form of student participation to contribute to the environment and the surrounding community. One of the issues in a sustainable village is creating a society that pays attention to the environment and achieves a clean and healthy life through the green society movement. The main goal of the Bojonegoro University KKN Tematik Kolaboratif 22nd group in 2023 in Tlogohaji Village, Sumberrejo District, Bojonegoro Regency, is towards a green society. To create a green society, various outreach, and counseling are carried out to increase awareness of community behavior towards better personal health and the environment. Some activities initiated include PHBS counseling and PPPK training at schools, counseling on the 3R concept for PKK, and planting trees in the village environment. With these various activities, it is hoped that the village community can apply clean, healthy behavior and care for the environment from a young age (children) to adulthood.